-2(7x+9)=-11

Simple and best practice solution for -2(7x+9)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7x+9)=-11 equation:


Simplifying
-2(7x + 9) = -11

Reorder the terms:
-2(9 + 7x) = -11
(9 * -2 + 7x * -2) = -11
(-18 + -14x) = -11

Solving
-18 + -14x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + -14x = -11 + 18

Combine like terms: -18 + 18 = 0
0 + -14x = -11 + 18
-14x = -11 + 18

Combine like terms: -11 + 18 = 7
-14x = 7

Divide each side by '-14'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| X+(X*0.2)=91000000 | | 3z-8=7[z-3] | | x=0.89 | | X+15=95 | | 2(-6x+6)=96 | | X+(X*0.2)=101167200 | | 6x^2-13xy-28y^2=0 | | X+(X*0.2)=12 | | y=0.18x^3-2.16x^2+4.86x | | t+7-13=-4 | | sin(3x-30)=0.6 | | 4A-20=22 | | -6(7+X)=-42 | | 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x |

Equations solver categories